Alluvial geoarchaeology floodplain archaeology and environmental change - Brown, Anthony G. 1958- (Cambridge Univ. Press, 1997)
This comprehensive manual is designed to give archaeologists the necessary background knowledge in environmental science required to excavate and analyse archaeological sites by rivers and on floodplains. Part I covers the techniques for studying alluvial environments, while Part II reviews the literature on the archaeology of alluvial environments. An important theme running through the book is the interaction between climatic and cultural forces and the transformation of riverine environments. Bringing together information on the evolution and exploitation of floodplain and river landscapes, it draws on examples from Britain, Europe, North America and Australasia. Alluvial geoarchaeology will also interest physical geographers, geologists and environmental scientists.
Keywords: Alluvium; Archeologie; Archäologie; Geografische aspecten; Milieuverandering; Overstromingen; Archaeological geology -- Methodology -- Handbooks, manuals, etc; Excavations (Archaeology) -- Handbooks, manuals, etc; Floodplain ecology -- Methodology -- Handbooks, manuals, etc; Soils -- Analysis -- Handbooks, manuals, etc; Water-saturated sites (Archaeology) -- Handbooks, manuals, etc; Methode; Schwemmland; Geoarchäologie